Preparation and application of resin-based crown ether composite adsorption material for removing trace metal ions in electronic-grade chemicals

By grafting crown ether in situ on spherical resin, resin-based crown ether composite adsorption material for electronic grade chemicals is prepared, which solves the problem of difficulty in removing trace amounts of multiple metal ions in the prior art, and achieves efficient and stable metal ion adsorption and removal effects.

CN119771365APending Publication Date: 2025-04-08FUZHOU UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510026549.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing adsorbent materials are difficult to effectively remove trace amounts of multiple metal ion impurities in electronic grade chemicals, and they have stability problems and limitations of a single adsorption site.

Method used

A resin-based crown ether composite adsorption material is prepared by grafting the crown ether by in-situ grafting, which is used to adsorb trace amounts of metal ions in electronic grade chemicals.

Benefits of technology

It realizes efficient adsorption and removal of trace metal ions in electronic grade chemicals, and the metal ion content can be reduced to less than 1 ppb, significantly improving the stability of the material and the adsorption capacity of polymetal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses preparation and application of a resin-based crown ether composite adsorption material for removing trace metal ions in electronic-grade chemicals, and belongs to the technical field of new application of new resin materials. The resin-based crown ether is prepared by taking resin and crown ether as raw materials through an in-situ grafting method, the resin-based crown ether is applied to the manufacturing process of electronic-grade chemicals as a composite adsorption material, and the content of all trace metal ions in the electronic-grade chemicals can be reduced to 1 ppb or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new resin materials and new applications, and specifically relates to a composite adsorption material prepared by in-situ grafting of crown ether with resin as a carrier and its application in adsorbing and removing trace metal ion impurities in the preparation process of electronic-grade chemicals. Background Art

[0002] Electronic-grade chemicals are indispensable raw materials in the electronics industry and are widely used in the production of electronic semiconductors and the manufacture of integrated circuits. Trace amounts of metal ion impurities are introduced into electronic-grade chemicals during preparation and transportation. Trace amounts of metal ion impurities will dissolve in the Si matrix or form silicides, leading to pn junction leakage, reduced reliability of gate dielectrics, and reduced quality of gate oxides in ICs. When certain electronic chemicals are used as electrolytes for lithium-ion batteries, metal ion impurities can damage the life of the battery. Therefore, it is particularly important to develop methods to effectively remove trace amounts of metal ion impurities in electronic-grade chemicals.

[0003] Among the many separation methods, adsorption has the advantages of simple process, easy control of conditions, and effective production without strict requirements on power equipment. In addition, due to the precise design of adsorption materials, it has become a very promising separation method. Currently, the widely used adsorption materials mainly include carbon materials, metal organic framework (MOF) materials, polymers, natural polymer compounds, etc. However, there are certain limitations in the application of these materials in electronic-grade chemicals. For example, MOF materials and composite metal oxide materials are prepared using metal salts, which will precipitate a large amount of metal ion impurities in electronic-grade organic solvents (strong solubility); polymer materials are unstable and will dissolve in electronic-grade chemicals, resulting in the inability to separate the adsorbent from the system; at the same time, existing adsorption materials usually contain only a single adsorption site, which cannot achieve the complete adsorption and removal of trace amounts of multiple metal ions. Therefore, it is crucial to develop and synthesize an adsorption material that can simultaneously adsorb and remove trace amounts of multiple metal ions in electronic-grade chemicals.

[0004] The invention uses a spherical resin which is easy to industrialize as a carrier, grafts a crown ether by an in-situ grafting method and uses the resin to adsorb and remove trace metal ion impurities in electronic-grade chemicals, thereby providing an effective adsorbent for removing trace metal ions in electronic-grade chemicals and having important significance for the purification of electronic-grade chemicals. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a composite adsorption material by in-situ grafting of crown ether with resin, and a new application of the method in removing trace metal ion impurities by adsorption in the preparation process of electronic grade chemicals.

[0006] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a resin-based crown ether composite adsorbent material for removing trace metal ions in electronic-grade chemicals comprises the following steps: (1) After soaking the resin in a solvent, a metal salt is added to carry out a chloromethylation reaction, and after the reaction is completed, the resin is washed with deionized water to obtain a chloromethylated resin; (2) Adding the crown ether into toluene to dissolve it under a nitrogen atmosphere, and then adding chloromethylated resin and triethylamine to react to obtain the resin-based crown ether composite adsorption material.

[0007] Furthermore, the resin used in step (1) is one of a styrene-based cation exchange resin and an acrylic acid-based cation exchange resin.

[0008] Furthermore, the solvent in step (1) is a mixture of 1,4-di(chloromethoxy)butane and carbon tetrachloride in a volume ratio of 1:1 to 1:10; and the soaking time is 0 to 36 hours.

[0009] Furthermore, the ratio of the mass of the resin used in step (1) to the volume of the solvent is 1 g:6 mL to 1 g:30 mL.

[0010] Furthermore, the metal salt in step (1) is a mixture of zinc chloride and sodium chloride; the mass ratio of the resin to zinc chloride and sodium chloride is 1:(0.1-5):(1-5).

[0011] Furthermore, the temperature of the chloromethylation reaction in step (1) is 25°C to 90°C, the rotation speed is 50 to 500 rpm, and the time is 0 to 48 hours.

[0012] Furthermore, the crown ether in step (2) is one of 4'-aminobenzo-15-crown-5-ether, 4'-aminobenzo-18-crown-6, 4',5'-diaminobenzo-15-crown-5, 4',5'-diaminobenzo-18-crown-6, 4',4"(5")-diaminodibenzo-15-crown-5, and 4',4"(5")-diaminodibenzo-18-crown-6.

[0013] Furthermore, the mass ratio of the chloromethylated resin to the crown ether used in step (2) is 5:1 to 1:10.

[0014] Furthermore, the ratio of the mass of the chloromethylated resin used in step (2) to the volume of triethylamine is 1 g:1 mL to 1 g:20 mL.

[0015] Furthermore, the reaction temperature in step (2) is 50°C to 120°C, the rotation speed is 50 to 300 rpm, and the time is 10 to 36 hours.

[0016] The resin-based crown ether composite adsorption material can be used for adsorbing and removing trace metal ions in electronic-grade chemicals.

[0017] Furthermore, the electronic-grade chemicals include N-methylpyrrolidone (NMP), isopropyl alcohol (IPA), propylene glycol methyl ether acetate (PMA), or ultra-clean high-purity wet electronic chemicals compounded thereof.

[0018] The advantages of the present invention are: The invention develops a composite material for adsorbing and removing trace metal ions in the preparation process of chemicals such as electronic-grade NMP, and the material can reduce the content of trace metal ions in electronic-grade chemicals to below 1 ppb. DETAILED DESCRIPTION

[0019] A resin-based crown ether composite adsorption material for removing trace metal ions in electronic-grade chemicals, the preparation of which comprises the following steps: (1) After soaking the resin in a mixed solution of 1,4-di(chloromethoxy)butane and carbon tetrachloride (1:1-1:10, v / v) for 0-36 hours, a mixture of zinc chloride and sodium chloride is added, and the reaction is carried out at 25°C-90°C and a rotation speed of 50-500 rpm for 0-48 hours. After the reaction is completed, the resin is washed with deionized water to obtain a chloromethylated resin; (2) At 50°C o The crown ether was added into toluene for dissolution at C~120 ℃, rotation speed 50~300 rpm and nitrogen atmosphere, and then chloromethylated resin and triethylamine were added and reacted for 10~36 hours to obtain a resin-based crown ether composite adsorption material.

[0020] The resin used in step (1) is one of a styrene-based cation exchange resin and an acrylic cation exchange resin. The mass ratio of the resin used to the volume of the solvent is 1 g:6 mL to 1 g:30 mL. The mass ratio of the resin used to zinc chloride and sodium chloride is 1:(0.1-5):(1-5).

[0021] The crown ether in step (2) is one of 4'-aminobenzo-15-crown-5-ether, 4'-aminobenzo-18-crown-6, 4',5'-diaminobenzo-15-crown-5, 4',5'-diaminobenzo-18-crown-6, 4',4"(5")-diaminodibenzo-15-crown-5, and 4',4"(5")-diaminodibenzo-18-crown-6. The mass ratio of the chloromethylated resin to the crown ether is 5:1 to 1:10. The mass ratio of the chloromethylated resin to the volume of triethylamine is 1 g:1 mL to 1 g:20 mL.

[0022] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0023] Example 1 10 g of 732 styrene cation exchange resin was added to a mixed solution consisting of 116.5 mL of carbon tetrachloride and 33.5 mL of 1,4-di(chloromethoxy)butane, and soaked at room temperature for 24 h. Then, 5 g of dry zinc chloride and 33.5 g of dry sodium chloride were added, and the reaction was carried out at 50 °C and 200 rpm for 14 h. After the reaction, the resin was washed with deionized water to obtain a chloromethylated resin. Then, 0.5 g of 4'-aminobenzo-15-crown-5-ether was added to 50 mL of toluene at 120 °C, 200 rpm and nitrogen atmosphere until dissolved. Then, 1 g of chloromethylated resin and 4 mL of triethylamine were added, and the reaction was carried out for 24 hours to obtain a crown ether-based resin composite adsorbent material.

[0024] Example 2 10 g of 732 styrene cation exchange resin was added to a mixed solution of 116.5 mL of carbon tetrachloride and 33.5 mL of 1,4-di(chloromethoxy)butane, and soaked at room temperature for 24 h. Then, 5 g of dry zinc chloride and 33.5 g of dry sodium chloride were added, and the reaction was carried out at 50 °C and 200 rpm for 14 h. After the reaction, the resin was washed with deionized water to obtain a chloromethylated resin. Then, 0.25 g of 4',5'-diaminobenzo-15-crown-5 was added to 50 mL of toluene at 120 °C, 200 rpm and nitrogen atmosphere until dissolved. Then, 1 g of chloromethylated resin and 4 mL of triethylamine were added, and the reaction was carried out for 24 hours to obtain a crown ether-based resin composite adsorbent material.

[0025] Example 3 10 g of 732 styrene cation exchange resin was added to a mixed solution of 116.5 mL of carbon tetrachloride and 33.5 mL of 1,4-di(chloromethoxy)butane, and soaked at room temperature for 24 h. Then, 5 g of dry zinc chloride and 33.5 g of dry sodium chloride were added, and the reaction was carried out at 50 °C and 200 rpm for 14 h. After the reaction, the resin was washed with deionized water to obtain a chloromethylated resin. Then, 1 g of 4',5'-diaminobenzo-15-crown-5 was added to 50 mL of toluene at 120 °C, 200 rpm and nitrogen atmosphere until dissolved. Then, 1 g of chloromethylated resin and 4 mL of triethylamine were added, and the reaction was carried out for 24 hours to obtain a crown ether-based resin composite adsorbent material.

[0026] Example 4 10 g of D001 acrylic acid cation exchange resin was added to a mixed solution of 116.5 mL of carbon tetrachloride and 33.5 mL of 1,4-di(chloromethoxy)butane, and soaked at room temperature for 24 h. Then, 5 g of dry zinc chloride and 33.5 g of dry sodium chloride were added, and the reaction was carried out at 50 °C and 200 rpm for 14 h. After the reaction, the resin was washed with deionized water to obtain a chloromethylated resin. Then, 0.5 g of 4'-aminobenzo-15-crown-5-ether was added to 50 mL of toluene at 120 °C, 200 rpm and nitrogen atmosphere until dissolved. Then, 1 g of chloromethylated resin and 4 mL of triethylamine were added, and the reaction was carried out for 24 hours to obtain a crown ether-based resin composite adsorbent material.

[0027] Example 5 10 g of D113 acrylic acid cation exchange resin was added to a mixed solution of 116.5 mL of carbon tetrachloride and 33.5 mL of 1,4-di(chloromethoxy)butane, and soaked at room temperature for 24 h. Then, 5 g of dry zinc chloride and 33.5 g of dry sodium chloride were added, and the reaction was carried out at 50 °C and 200 rpm for 14 h. After the reaction, the resin was washed with deionized water to obtain a chloromethylated resin. Then, 0.5 g of 4'-aminobenzo-15-crown-5-ether was added to 50 mL of toluene at 120 °C, 200 rpm and nitrogen atmosphere until dissolved. Then, 1 g of chloromethylated resin and 4 mL of triethylamine were added, and the reaction was carried out for 24 hours to obtain a crown ether-based resin composite adsorbent material.

[0028] Example 6 10 g of 732 styrene cation exchange resin was added to a mixed solution of 116.5 mL of carbon tetrachloride and 33.5 mL of 1,4-di(chloromethoxy)butane, and soaked at room temperature for 24 h. Then, 5 g of dry zinc chloride and 33.5 g of dry sodium chloride were added, and the reaction was carried out at 50 °C and 200 rpm for 14 h. After the reaction, the resin was washed with deionized water to obtain a chloromethylated resin. Then, 1 g of 4′,4″(5″)-diaminodibenzo-15-crown-5 was added to 50 mL of toluene at 120 °C, 200 rpm and nitrogen atmosphere until dissolved. Then, 1 g of the chloromethylated resin and 4 mL of triethylamine were added, and the reaction was carried out for 24 hours to obtain a crown ether-based resin composite adsorbent.

[0029] The resin raw material used in the embodiment and the obtained composite adsorption material were subjected to an adsorption experiment using a dynamic fixed bed. The specific operation was as follows: about 4.7 mL of the pretreated resin material was loaded into the fixed bed adsorption column, and the corresponding loading flow rate was 14.0 BV / h; then a certain concentration of NMP solution was pumped into the fixed bed adsorption column at a flow rate of 1.1 mL / min, and the metal ion concentration in the NMP solution at the discharge port was tested by ICP-MS (Thermo Fisher, ICAP RQ). The results are shown in Table 1.

[0030] The pretreatment of resin materials includes the following steps: ①First, soak and clean the resin material with ultrapure water (18.2 MΩ, TOC <2 ppb), then soak and clean it with a 1~6 M hydrochloric acid solution, and then clean it with ultrapure water until it is neutral. Then, soak and clean it with a 1~6 M tetramethylammonium hydroxide solution, and then clean it with ultrapure water until it is neutral. Finally, soak and clean it with a 1~6 M hydrochloric acid solution, and then clean it with ultrapure water until it is neutral. ② Repeat step ① 3~4 times; ③ After filtering out the water, the cleaned resin material is stored in a polytetrafluoroethylene (PFA) bottle and placed in a clean laboratory for standby use (the pretreatment process and adsorption process of the adsorption material are both performed in a clean laboratory).

[0031] Table 1 Concentration of metal ions in NMP after adsorption treatment

[0032] As can be seen from Table 1, the crown ether-based resin composite adsorption material prepared in the example can significantly reduce the concentration of various metal ions in NMP to less than 1 ppb.

[0033] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a resin-based crown ether composite adsorbent material for removing trace metal ions from electronic-grade chemicals, characterized in that: The following steps are involved: (1) After soaking the resin in a solvent, a metal salt is added to carry out a chloromethylation reaction, and after the reaction is completed, the resin is washed with deionized water to obtain a chloromethylated resin; (2) Adding the crown ether into toluene to dissolve it under a nitrogen atmosphere, and then adding chloromethylated resin and triethylamine to react to obtain the resin-based crown ether composite adsorption material.

2. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The resin used in step (1) is one of a styrene-based cation exchange resin and an acrylic acid-based cation exchange resin.

3. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The solvent in step (1) is prepared by mixing 1,4-di(chloromethoxy)butane and carbon tetrachloride in a volume ratio of 1:1 to 1:10; the soaking time is 0 to 36 hours.

4. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The metal salt in step (1) is a mixture of zinc chloride and sodium chloride; the mass ratio of the resin to zinc chloride and sodium chloride is 1:(0.1-5):(1-5).

5. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The temperature of the chloromethylation reaction in step (1) is 25°C to 90°C, and the time is 0 to 48 hours.

6. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The crown ether in step (2) is one of 4'-aminobenzo-15-crown-5-ether, 4'-aminobenzo-18-crown-6, 4',5'-diaminobenzo-15-crown-5, 4',5'-diaminobenzo-18-crown-6, 4',4"(5")-diaminodibenzo-15-crown-5 and 4',4"(5")-diaminodibenzo-18-crown-6.

7. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The mass ratio of the chloromethylated resin to the crown ether used in step (2) is 5:1 to 1:

10.

8. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The ratio of the mass of the chloromethylated resin used in step (2) to the volume of triethylamine is 1 g:1 mL to 1 g:20 mL.

9. The method for preparing the resin-based crown ether composite adsorption material according to claim 1, characterized in that: The reaction temperature in step (2) is 50°C to 120°C, and the reaction time is 10 to 36 hours.

10. Use of the resin-based crown ether composite adsorbent material as claimed in claim 1 in the adsorption and removal of trace metal ions in electronic grade chemicals, characterized in that: The electronic grade chemicals include N-methyl pyrrolidone, isopropyl alcohol, and propylene glycol methyl ether acetate.

Citation Information

Patent Citations

  • Benzo crown ether graft polymer material with lithium isotope separation effect and preparation method thereof

    CN102911372A

  • Chelating resin for capturing electronic-grade hexafluorobutadiene metal ions and preparation method thereof

    CN115260401A

  • Lithium extraction adsorbent as well as preparation method and application thereof

    CN117839651A

  • An efficient and environment friendly process for chloromethylation of substituted benzenes

    IN201921023761A

  • Trichloromethylated aromatic

    US2945894A